2006
DOI: 10.1038/nprot.2006.49
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of chelating agents to proteins and radiolabeling with trivalent metallic isotopes

Abstract: Peptides and proteins may be tagged with metallic elements in order to use them as imaging reporters or for other applications. The polypeptide of interest is first conjugated to a suitable chelating agent that forms stable complexes with the element of interest. This conjugation step is undertaken either in aqueous or in non-aqueous conditions depending on the solubility of the substrate. For polypeptides of greater than approximately 10 kDa in size, this is normally done in aqueous medium. Most commonly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 3 publications
0
54
0
10
Order By: Relevance
“…64 Cu (t 1/2 = 12.7h), with both β + and β − emissions, allows for both PET imaging and radionuclide therapy, and 64 Cu labeled antibodies have attracted considerable interest in the field of targeted radionuclide therapy and diagnosis. In addition, copper has several other medically relevant isotopes ( 60 Cu, 61 Cu, 62 Cu and 67 Cu) that are potentially useful for either diagnosis or therapy 2,3 . Although direct labeling approaches for labeling antibodies with 64 Cu have been proposed 4 , indirect labeling using a BFC is the preferred method to control stability of the 64 Cu-antibody complex formed.…”
Section: Introductionmentioning
confidence: 99%
“…64 Cu (t 1/2 = 12.7h), with both β + and β − emissions, allows for both PET imaging and radionuclide therapy, and 64 Cu labeled antibodies have attracted considerable interest in the field of targeted radionuclide therapy and diagnosis. In addition, copper has several other medically relevant isotopes ( 60 Cu, 61 Cu, 62 Cu and 67 Cu) that are potentially useful for either diagnosis or therapy 2,3 . Although direct labeling approaches for labeling antibodies with 64 Cu have been proposed 4 , indirect labeling using a BFC is the preferred method to control stability of the 64 Cu-antibody complex formed.…”
Section: Introductionmentioning
confidence: 99%
“…Considering an initial antibody concentration of 5 mg/mL, it obtained a protein recovery above 83±1.42% (N = 15). These results demonstrated that the method applied for purification of immunoconjugate was more reproducible than the method described in the literature (Cooper, Sabbah, Mather, 2006), which results are variable due to the loss of protein (10 -50%).…”
Section: Analysis Of the Protein Concentration Of The Immunoconjugatementioning
confidence: 68%
“…The distribution of radioactivity in the chromatographic plate was performed by radiochromatography (radio-TLC Imaging Scanner AR-2000, Eckert & Ziegler / USA) (Chang, Smith, Lapi, 2013). The radiochemical purity was also evaluated by HPLC (Agilent, detector UV 190-300 nm) (Cooper, Sabbah, Mather, 2006;Chang, Smith, Lapi, 2013), using the same methodology as described above.…”
Section: Radiolabeling Development and Analysis Of Specific Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…11 Briefly, using this method, the protein is stripped of metal ions using EDTA and then the buffer exchanged into 0.1 mol/L HEPES buffer pH 8.9 by ultracentrifugation. p-SCN-Bn-NOTA (as a 40-fold molar excess to protein) in dimethyl sulfoxide is added, and the conjugation is allowed to proceed at ambient temperature for 3 hours.…”
Section: Labeling Of the Molecular Imaging Biomarkermentioning
confidence: 99%